Nonlinear dissipative slip flow of Jeffrey nanomaterial towards a curved surface with entropy generation and activation energy - Khan, M. Ijaz; Alzahrani, Faris (Mathematics and computers in simulation, 2021)
In this research work, mathematical modeling for steady magnetized two-dimensional (2D) incompressible flow of Jeffrey nanofluid is developed over a stretched curved surface with combined characteristics of activation energy, Brownian motion, viscous dissipation, nonlinear mixed convection, magnetohydrodynamics (MHD), Joule heating and thermophoresis diffusion. Velocity slip condition is further imposed on the curved stretched boundary. Total entropy generation rate which depends on the velocity, temperature and concentration fields is obtained via second law of thermodynamics. The dimensional differential equations are altered into dimensionless ordinary differential system by using appropriate similarity variables. The obtain system of dimensionless differential equations are solved numerically through Built-in-Shooting method. The influence of sundry flow variables associated with this problem like curvature parameter, velocity slip parameter, Deborah number, thermophoresis diffusion, Prandtl number, Brownian motion, chemical reaction, Brinkman number and activation energy are sketched for entropy generation rate, concentration, temperature and velocity field. Furthermore, Nusselt number and skin friction coefficient are calculated numerically in the presence of Deborah number, slip parameter, thermophoresis parameter, Eckert number and Brownian diffusion parameter. It is noted that velocity field is an increasing function of curvature parameter, while contrast impact is observed for Deborah number and velocity slip parameter. It is also seen that the magnitude of skin friction upsurges versus Deborah number while decays against relaxation time. Nusselt number is increased via larger Eckert number and declines against thermophoretic parameter.